The just war revisited - O'Donovan, Oliver (Cambridge, Cambridge University Press, 2003)
With Christian views differing widely on the morality of war, this book seriously re-examines ethical questions of contemporary urgency. The text covers the use of biological and nuclear weapons, military intervention, economic sanctions, and the role of the U.N. Opening with a challenging dedication to the new Archbishop of Canterbury, it proceeds to analyze vital topics which the Archbishop and others will find relevant to the discussion of the ethics of warfare.
Just war revisited. Antagonistic praxis and evangelical counter-praxis ; Authority ; Discrimination ; Differences of proportion -- Counter-insurgency war -- Immoral weapons -- War by other means -- Can war-crimes trials be morally satisfying? -- Afterword: without authority.
Includes bibliographical references and index.
Keywords: War -- Religious aspects -- Christianity